The Sunshade Chapel of Meritaten from the House-of-Waenre of Akhenaten - Wegner, Josef W. 1967- (University Museum monograph, 2017)
The quartzite architectural block E16230 has been on display in the Penn Museum for 115 years. E16230 is one of the few large architectural pieces in the world surviving from the much-debated reign of the "heretic" king Akhenaten. This block is one of the most historically significant objects on display in the Egyptian galleries, yet it has never been analyzed or published. This volume addresses that glaring gap and provides for the first time a translation and discussion of the important texts on the object, along with analysis of the architectural evidence it provides.The block is part of the once intensely ornamented façade of a solar chapel ("sunshade") dedicated to princess Meritaten, the eldest daughter of Akhenaten and Nefertiti. The large (1100 kg) block originates in a chapel that was part of a royal ceremonial palace of Akhenaten named Per-Waenre ("the house of the Unique-one-of-Re").